THE SMES IN ORDER TO FACE THE AFTA AND GLOBALIZATION ERA - Gita Arasy Herwida (InFestasi, 2007)
Small and medium enterprises (SMEs) have contributedmuch to the growth of the economy in Indonesia. Further, this sector isalso famous for its survival during the economic crisis in the late 1990’sor specifically the crisis began in the late 1997. The survival of theSMEs in Indonesia from that crisis has alerted the government andeconomic societies for not only concerning the economic developmentto the large enterprises as most of those large enterprises werecollapsed during the crisis. Prior the crisis, the government focusedon the development in capital tight industrial sectors in a big capitalsuch as: in banking and manufacturing for mass production. Most ofpolicies that were issued at that time enhanced the development ofthis sector such as: policies that eased inward investment in someparticular business; policies to provide value added tax exemption inthe bounded zone area, etc.If we look back to the crisis time, the collapse of the large enterpriseswas mainly caused by their lack of ability in paying their overseasdebt, which was in US dollar currency. The SMEs could survive mainlybecause of two reasons. First, the SMEs’ business is mostly exportoriented. They gained advantage from the payment which was in USdollar. The foreign exchange of US dollar to Indonesian currency,Rupiah, during the crisis was increased amazingly more than fourtimes from the previous value. Second, most of the SMEs did not haveliability with the foreign banks or foreign parties. Thus, they did nothave to pay any liabilities in US dollar. This was in contrast to thelarge enterprises which mostly had liability with the foreign banks orparties. They had responsibility to give payment in US dollar whichmeant that their liability amount rose parallel to the increasing of USdollar’s value. The flexibility of the SMEs in their working capitalside was one of their key factors in their survival from the crisis. TheSMEs do not rely on their all working capital on foreign debt, they usetheir own capital or may have debt from local sources.Actually the government has already established a new department inregard to the development of the SMEs. The department is under theMinistry of Coopertives and Small Enterprises which was establishedin 1993. This department has also issued some policies and strategicprograms for the development of the SMEs and the cooperatives sectorin Indonesia. The core objective of the establishment of this departmentwas to overcome the difficulties which were faced, either externally orinternally. However, the crisis effectively encouraged the governmentto give more attention to the SMEs. This was in terms of giving themmore opportunity to grow further to become strong large entities, ratherthan merely remaining at the small and medium stage. Another fact isthat the SMEs are able to provide wide job opportunities, whichIndonesia requires to deal with the increasing number of unemployment.